The effect of sleep quality on cognitive function among Ipoh young adults / Syed Murshid Syed Zubir ... [et al.] - Syed Zubir, Syed Murshid; Syed Mud Puad, Sharifah Maimunah; Abu Kassim, Nurul Ain; Md Yusoff, Yusandra (Universiti Teknologi MARA, 2023)
A good sleep quality enhances both physiological and psychological functions. Despite the importance of sleep quality, it is one of the common issues faced by the young population due to modern lifestyle. The main purpose of this study is to investigate the effect of sleep quality on cognitive function (working memory and executive function) among Ipoh young adults. A total of thirty-two (n=32) healthy male Ipoh young adults aged (21.0 ± 1.0) years old participated in this study. The sleep quality was measured using Pittsburgh Sleep Quality Index (PQSI). Meanwhile, for cognitive function the N-Back task was used to measure working memory and the Wisconsin Sorting Card Test (WSCT) was used to measure executive function. The results of this study showed a significant effect of sleep quality on working memory (0Back p = 0.011, 1-Back p = 0.001, 2 Back p = 0.008) and executive function (Category Achievement p = 0.001, Total Errors p = 0.010). These findings demonstrated sufficient evidence that sleep quality affects cognitive function (p < .05). Hence, sleep quality is associated with better cognitive function in young adults